2022
DOI: 10.1002/jmor.21518
|View full text |Cite
|
Sign up to set email alerts
|

How to stay attached—Formation of the ricefish plug and changes of internal reproductive structures in the pelvic brooding ricefish, Oryzias eversi Herder et al. (2012) (Beloniformes: Adrianichthyidae)

Abstract: Teleost fishes show an enormous diversity of parental care, ranging from no care to viviparity with maternal provisioning of embryos. External brooders carry their developing eggs attached to their bodies. This requires the formation of novel morphological structures to support attachment. The pelvic brooding ricefish Oryzias eversi evolved such a structure, called the "plug." The plug anchors attaching filaments from the fertilized eggs inside the female reproductive system, allowing the female to carry the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The success of viviparity requires the regulation of the local immune and inflammatory response (Mor et al, 2017). No other references on immunotolerance responses in viviparous teleosts were found; however, there are studies that describe the characteristics of the leukocyte infiltrate and its implication in the immunological responses in the ovary during reproductive season (Gardiner, 1978; Koya et al, 1997; Schüller et al, 2022). Here, we observed that, during the nongestation stage, a variety of lymphocytes, EGCs, fibroblasts, MMCs and tissue debris was found in the lamina propria of some ovarian folds.…”
Section: Discussionmentioning
confidence: 99%
“…The success of viviparity requires the regulation of the local immune and inflammatory response (Mor et al, 2017). No other references on immunotolerance responses in viviparous teleosts were found; however, there are studies that describe the characteristics of the leukocyte infiltrate and its implication in the immunological responses in the ovary during reproductive season (Gardiner, 1978; Koya et al, 1997; Schüller et al, 2022). Here, we observed that, during the nongestation stage, a variety of lymphocytes, EGCs, fibroblasts, MMCs and tissue debris was found in the lamina propria of some ovarian folds.…”
Section: Discussionmentioning
confidence: 99%
“…Here, females carry the cluster of fertilized eggs on their ventral side until the embryos hatch. Pelvic brooding comes with a set of adaptations that include a novel egg‐anchoring tissue (Hilgers et al., 2022 ; Iwamatsu et al., 2008 ; Schüller et al., 2022 ), shorter ribs that create a ventral concavity into which the fertilized eggs are placed (Kottelat, 1990b ; Popta, 1905 ; Spanke et al., 2021 ), and elongated pelvic fins that cover the eggs and ventral concavity (Figure 1 ). Adaptations to pelvic brooding are thus female‐biased, resulting in a pronounced sexual dimorphism.…”
Section: Introductionmentioning
confidence: 99%